Perencanaan Desain Beton Berpori dengan Penambahan Fly Ash untuk Jalan Lalu Lintas Rendah - Sherryva Anique Michella; Purwo Mahardi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Porous concrete is a type of pavement material with interconnected cavities that allow rainwater to seep directly into the ground. This material is widely used on roads with low traffic volumes because it helps reduce puddles and surface runoff. This study was conducted to analyze the effect of using fly ash as a partial cement substitute on the characteristics of porous concrete. Variations in fly ash content were 10%, 20%, and 25% of the cement weight. Parameters analyzed included workability, permeability, and compressive strength at 7, 14, and 28 days. The research method involved mix design, specimen preparation, and laboratory testing of fresh and hardened concrete. Test results showed that the addition of fly ash affected all parameters of porous concrete. Higher fly ash content tended to increase the concrete's water permeability, but decreased its compressive strength. The 20% fly ash variation provided the most balanced results, maintaining good workability, high permeability, and compressive strength that met the requirements for low-traffic roads. The use of fly ash is also considered to support the concept of sustainable development because it can reduce cement use and utilize waste from coal combustion. Thus, porous concrete with fly ash substitution has the potential to be an environmentally friendly alternative pavement material suitable for use on neighborhood roads, parking areas, and facilities with light traffic loads.